Dynamics of HBV cccDNA expression and transcription in different cell growth phase - Chong, Chin-Liew (BioMed Central, 2011)
BACKGROUND: The covalently closed-circular DNA (cccDNA) of hepatitis B virus (HBV) is associated with viral persistence in HBV-infected hepatocytes. However, the regulation of cccDNA and its transcription in the host cells at different growth stages is not well understood. METHODS: We took advantages of a stably HBV-producing cell line, 1.3ES2, and examine the dynamic changes of HBV cccDNA, viral transcripts, and viral replication intermediates in different cellular growth stages. RESULTS: In this study, we showed that cccDNA increased suddenly in the initial proliferation phase of cell growth, probably attributable to its nuclear replenishment by intracellular nucleocapsids. The amount of cccDNA then decreased dramatically in the cells during their exponential proliferation similar to the loss of extrachromosomal plasmid DNA during cell division, after which it accumulated gradually while the host cells grew to confluency. We found that cccDNA was reduced in dividing cells and could be removed when proliferating cells were subjected to long term of lamivudine (3TC) treatment. The amounts of viral replicative intermediates were rapidly reduced in these proliferating cells and were significantly increased after cells reaching confluency. The expression levels of viral transcripts were increased in parallel with the elevated expression of hepatic transcription factors (HNF4α, CEBPα, PPARα, etc.) during cell growth confluency. The HBV transcripts were transcribed from both integrated viral genome and cccDNA, however the transcriptional abilities of cccDNA was less efficient then that from integrated viral genome in all cell growth stages. We also noted increases in the accumulation of intracellular viral particles and the secretion of mature virions as the cells reached confluency and ceased to grow. CONCLUSIONS: Based on the dynamics of HBV replication, we propose that HBV replication is modulated differently in the different stages of cell growth, and can be divided into three phases (initial proliferation phase, exponential proliferation phase and growth confluency phase) according to the cell growth curve. The regulation of cccDNA in different cell growth phase and its importance regarding HBV replication are discussed.